2006
DOI: 10.1242/dev.02543
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43-mediated modulation of polarized cell movement and the directional migration of cardiac neural crest cells

Abstract: Connexin 43 knockout (Cx43␣1KO) mice have conotruncal heart defects that are associated with a reduction in the abundance of cardiac neural crest cells (CNCs) targeted to the heart. In this study, we show CNCs can respond to changing fibronectin matrix density by adjusting their migratory behavior, with directionality increasing and speed decreasing with increasing fibronectin density. However, compared with wild-type CNCs, Cx43␣1KO CNCs show reduced directionality and speed, while CNCs overexpressing Cx43␣1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 46 publications
13
149
1
1
Order By: Relevance
“…In some systems both effects, regulation of the cytoskeleton and migration, have been observed [Iacobas et al, 2003;Xu et al, 2006;Elias et al, 2007]. This strengthens the notion of a functional relationship of Cxs and the cytoskeleton and we will peruse this further in the following chapter.…”
Section: Connexin Function In Regulation Of Cell Migrationsupporting
confidence: 66%
See 3 more Smart Citations
“…In some systems both effects, regulation of the cytoskeleton and migration, have been observed [Iacobas et al, 2003;Xu et al, 2006;Elias et al, 2007]. This strengthens the notion of a functional relationship of Cxs and the cytoskeleton and we will peruse this further in the following chapter.…”
Section: Connexin Function In Regulation Of Cell Migrationsupporting
confidence: 66%
“…Association of Cx43 and drebrin was confirmed by an independent study, where regions of co-localization were abundantly found at areas of cell-cell contact and along cell processes [Xu et al, 2006]. These data suggest that drebrin is a strong candidate for interaction with Cx43 and might prevent Cx degradation thereby playing an important for maintaining Cx43 plaques in situ at the plasma membrane.…”
Section: Drebrin (Developmentally Regulated Brain Protein)mentioning
confidence: 53%
See 2 more Smart Citations
“…Increased cell protrusive activity, loss of polarized cell movement, rearrangement of actin stress fibers (Xu et al, 2006) Total Die at birth from severe pulmonary outflow tract obstruction (Reaume et al, 1995) PECAM-1 Cell-cell adhesion In vitro studies of cells froom knockout mice…”
Section: Note On Nomenclaturementioning
confidence: 99%